Prevalence of low back pain in different educational levels: a systematic review - Alexandre Apolinário de Souza Batista; Nicholas Henschke; Vinícius Cunha Oliveira
Abstract Introduction: Non-specific low back pain (LBP) can be understood through the interaction of biopsychosocial factors such as education. Unfortunately, it remains unclear whether education can be considered an important risk and prognostic factor for the occurrence of LBP. Objective: To investigate the association between education and LBP. Methods: The following databases were searched: MEDLINE, EMBASE, Cochrane, AMED and PsyINFO. Results: Thirteen studies were included in the review. The Prevalence Critical Appraisal Instrument (PCAI) was used to assess risk of bias. Methodological quality scores ranged from 7 to 10 on a scale of 0-10. There was a 23% (95% CI, 13-37) prevalence of LBP (10,582 out of a total of 99,457 cases) in the general sample at the time of assessment. The meta-analysis of studies on the prevalence of LBP in people with low, medium or high educational level found the following results, respectively: 24% (95% CI, 12-43), 27% (95% CI, 9-56), and 18% (95% CI, 5-50). The meta-regression identified heterogeneity among the studies included in the review. This can be explained by educational differences (p < 0.05). Conclusion: Occurrence of LBP varies according to educational level. Individuals with higher educational levels are less often affected by LBP than individuals with medium or low educational levels.